Penerapan Audit Kepatuhan Terhadap Transparansi Dana Kampanye Partai X Kota Y Dalam Pemilihan Umum - Revi Ardiana Putri; Hero Priono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study was conducted to obtain the level of compliance and transparency of Political Parties in the examination of campaign funds, by selecting objects at Party X in City Y. A descriptive qualitative approach was used to analyze various aspects of compliance, including understanding regulations, recording transactions, and reporting campaign funds. The findings of this study indicate that Party X in City Y has not fully understood the General Election Commission Regulation (PKPU) Number 18 of 2023 related to campaign finance reporting. This results in a lack of transparency of receipts and expenditures. Thus, increasing transparency over political party campaign finance reports is not only a legal imperative, but also an investment in maintaining the integrity of a healthy and strong democracy.